2008
DOI: 10.1002/pd.2137
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex ligation‐dependent probe amplification (MLPA) in prenatal diagnosis—experience of a large series of rapid testing for aneuploidy of chromosomes 13, 18, 21, X, and Y

Abstract: The data presented confirm that MLPA is a rapid, simple and reliable method for large scale testing for nonmosaic aneuploidy of chromosomes 13, 18, 21, X, or Y in trypsin-digested CVS and in AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…In many publications, the sensitivity and specificity of the MLPA method, regarding the identification of the most frequent rearrangements, amounted to 100% [31,32,40]. The frequency of failures resulting, among others, from poor DNA quality varied from 0.8% to 4.4% [30][31][32]. Many authors emphasise the fact that the MLPA method is sensitive to DNA quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many publications, the sensitivity and specificity of the MLPA method, regarding the identification of the most frequent rearrangements, amounted to 100% [31,32,40]. The frequency of failures resulting, among others, from poor DNA quality varied from 0.8% to 4.4% [30][31][32]. Many authors emphasise the fact that the MLPA method is sensitive to DNA quality.…”
Section: Discussionmentioning
confidence: 99%
“…Tests that enable the identification of selected chromosome aberrations by other methods are increasingly common: FISH (fluorescence in situ hybridization), QF-PCR (quantitative fluorescence polymerase chain reaction), and MLPA (multiplex ligation-dependent probe amplification) [20][21][22][23][24][25][26][27][28][29][30][31][32]. These methods, having comparable efficacy and diagnostic reliability, making it possible to diagnose SHOX gene rearrangements [33].…”
Section: Diagnosticsmentioning
confidence: 99%
“…Sequences showing aberrant copy numbers are identified by comparing the peak pattern obtained to that of reference samples. MLPA analyses were performed using the SALSA MLPA kit P095 Aneuploidy (MRC-Holland, Amsterdam, The Netherlands), containing probes designed to detect aneuploidy of chromosomes 13, 18, 21, X, and Y [20]. Information on the localization, sequences, and lengths of the probes is available on the MRC-Holland website (https://www.mlpa.com/WebForms/WebFormProductDetails.aspx?Tag = _tz2fAPIAupKyMjaDF-E-t9bmuxqlhe_Lgqfk8Hkjuss.&ProductOID = _b4E4JKHdVds).…”
Section: Methodsmentioning
confidence: 99%
“…It was introduced in clinical practice to rapidly detect aneuploidies of chromosomes 13, 18, 21, X, and Y in prenatal screening [17,18,19,20]. Here, for the first time, we used MLPA to screen for putative X aneuploidies and X structural abnormalities in the postnatal period.…”
Section: Introductionmentioning
confidence: 99%
“…With TK, a wide range of chromosomal abnormalities can be detected, including alterations in copy number (aneuploidy) and structural chromosomal rearrangements such as translocations and inversions, being either balanced or unbalanced. Targeted PCR-based assays such as multiplex ligation-dependent probe amplification (MLPA) or quantitative fluorescent PCR (QF-PCR), are highly suited for rapid aneuploidy detection (RAD) of the chromosomes 21, 18, 13, X and Y [4-12]. Previously, it has been suggested that if the referral reason is an increased risk of Down's syndrome, resulting from a positive screening test result or an advanced maternal age, karyotyping could effectively be replaced by RAD, provided that no structural fetal abnormality has been detected upon ultrasound examination [5,13-17].…”
Section: Introductionmentioning
confidence: 99%